Hubungan Hiperglikemia Reaktif dengan Prognostik Stroke Iskemik di Rumah Sakit Budi Kemuliaan Kota Batam - Yusmahenry Galindra; Sukma Sahreni; Zilvina Andjellya (Universitas Batam, 2022)
Background:Stroke is the process of death from brain cells due to lack of oxygen supply to the brain. An ischemic stroke is an episode of neurological dysfunction caused by focal, spinal, or focal cerebral infarction. Stroke is the second leading cause of death in the world and the third cause of disability in the world. There are many factors that are thought to play a role in the onset of stroke, one of which is hyperglycemia. The purpose of this study is to find out the relationship of reactive hyperglycemia with ischemic stroke prognostics at Budi Kemuliaan hospital in Batam city in 2020-2021. Method:Observasional analytic research with aproaching cross sectional that is done at RSBK in Batam City On December 2021. In this study, the population is all ischemic stroke patients recorded in medical records at Budi Kemuliaan Hospital Batam for the period August 2020 - July 2021.The technique of tacking sample is purpossive samply with the number of samples are 107. The result of resorser analysed with frequency distribution, tabulated crosswise then examined with chi-square. Result:The result of analysis chi-square is obtained p= 0,003 where p is smaller than with significancy level alfa = 5% (0,05). Conclusion:There is the relationship between reavtive hyperglycemia with prognostik of ischemic stroke at RSBK Batam city.